Dental Implants Loaded With Bioactive Agents Promote Osseointegration in Osteoporosis: A Review - Zhang, Cheng; Zhang, Tianjia; Geng, Tengyu; Wang, Xudong; Lin, Kaili; Wang, Penglai (Frontiers in Bioengineering and Biotechnology, 2021)
Implant denture is widely used in patients with dentition defect or loss, which has higher chewing efficiency and will not damage the adjacent teeth, compared to the fixed or removable denture. Till now, implant denture is still at risk of failure in some systemic diseases, including osteoporosis, due to non-ideal local microenvironment. Ordinary physical and chemical modifications are used to change the roughness of implant surface to promote osseointegration, however, their effect is limited in osteoporotic patients. Recently, many researchers focus on the study of bioactive modification of implant and have amount promising results. Herein, we summarize the progress in bioactive modification strategy for promoting osseointegration via regulating the local osteoporotic microenvironment.